Quantitative analysis of Scratch assay and Colony formation assay data using MATLAB - Ingrová, Kateřina; Chmelíková, Larisa; Zumberg, Inna (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
Utilizing Scratch and Colony formation assays is crucial for understanding cell migration and proliferation dynamics. In this study, we present novel approaches utilizing MATLAB for the processing of images obtained from these assays. We demonstrate the effectiveness of our approaches through validation experiments on human osteosarcoma SaOS-2 cells, showcasing their applicability across different experimental conditions. Moreover, the inhibitory effect of two concentrations of gentamicin (0.1 mg/ml, 0.3 mg/ml) on the migration and clonogenicity of SaOS-2 cells was declared.
Keywords: Gentamicin; SaOS-2; Scratch assay; Colony formation assay; MATLAB